TRANSFORMASI VISUAL PRODUK UMKM MELALUI TEKNOLOGI AI: STUDI KASUS NASABAH PNM DESA SUNGAI NILAU KABUPATEN MERANGIN - Tulus Akbar; Adri Flouren Timor.S; Nabila Sasgita; Habibi; Mukhlis Yunus; Yusrizal (AbdiMasya | Hira Institute, 2026)
Artificial intelligence (AI) offers practical opportunities for micro, small, and medium enterprises (MSMEs) to improve product visuals efficiently and affordably. This community service program aimed to strengthen the knowledge and skills of PT Permodalan Nasional Madani (PNM) clients in Sungai Nilau Village, Merangin Regency, in using AI to create attractive and professional product images for digital marketing. The program employed Participatory Action Research through needs identification, socialization, practical training, and evaluation. Sixteen culinary MSME owners participated, most of whom produced gelamai, a traditional food of Merangin Regency. Evaluation was conducted through direct observation during practice and monitoring of participants’ work shared in a WhatsApp group. Initial findings showed that 81% of participants had never used AI technology. After the program, 94% understood the material and were able to apply it in product visual development. In addition, 57% considered the material and practice relevant to their business needs, while 37% were able to produce visual innovations independently. These results indicate that practical AI training improved participants’ digital literacy and basic skills in developing product visuals for more competitive online product promotion.